Theocritus space, absence, and desire - Thalmann, William G. 1947- (Oxford scholarship online, 2023)
Discusses many of Theocritus's Idylls with emphasis on how these poems construct space - its contours and borders, along with the people, animals, and objects that fill it - and the equally important role of absence